2021
DOI: 10.1089/g4h.2019.0180
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Activity and Exergaming on Motor Skills and Executive Functions in Children with Autism Spectrum Disorder

Abstract: Objective: This study aims at investigating the effects of two types of interventions, Sports, Play and Active Recreation for Kids (SPARK) and exergaming (Kinect), on motor skills (MS) and executive functions (EF) in children with autism spectrum disorder (ASD). Materials and Methods: Sixty children, aged 6-10 years were randomly assigned to SPARK (n = 20), Kinect (n = 20), or a control group (n = 20). Children's MS and EF were assessed before and after the intervention. The SPARK and Kinect groups participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 58 publications
(110 reference statements)
2
40
0
7
Order By: Relevance
“…A total of four studies used a sample size greater than 50 subjects [68,90,93,94]; 50% of the studies reported participants who terminated the intervention before the hypothesized end [67,68,85,86,92,[95][96][97][98][99][100] with drop-out percentages ranging from 5,5% [86] to 45,8% [96]. Data lost during the study were in some cases analyzed by applying the principle of Intention To Treat (ITT) that resulted in a percentage of data lost ranging from 6% [94] to 26% [68].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…A total of four studies used a sample size greater than 50 subjects [68,90,93,94]; 50% of the studies reported participants who terminated the intervention before the hypothesized end [67,68,85,86,92,[95][96][97][98][99][100] with drop-out percentages ranging from 5,5% [86] to 45,8% [96]. Data lost during the study were in some cases analyzed by applying the principle of Intention To Treat (ITT) that resulted in a percentage of data lost ranging from 6% [94] to 26% [68].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Overall, most studies reported that exergaming produced several benefits for young individuals diagnosed with ASD. Collins et al (2015), Flynn and Colon (2016), Rafiei Milajerdi et al (2020) all noted improvements in EF following their exergame-based interventions. Both Collins and Hilton utilised the Behaviour Rating Inventory of Executive Function (BRIEF) to measure changes in EF and both observed improvements in all areas of the inventory.…”
Section: Study Findingsmentioning
confidence: 93%
“…However, two were within-subject experimental designs with an A-B-A exposure (Anderson-Hanley et al, 2011;Chung et al, 2015), one was a two-arm parallel single-blinded trial (Lau et al, 2020), and another was a mixedmethods observational study (Pope et al, 2019). Only one study included in this review was a randomised controlled trial (Rafiei Milajerdi et al, 2020). The BRIEF overall score, the global executive composite, showed a significant improvement (p < .05).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations